Identification of the risks of consumer credit cooperatives - V. Yu Didenko; N. I. Morozko; N. I. Morozko (Вестник университета)
Various types of classification of risks of credit consumer cooperatives have been considered. The author’s approach to the classification of cooperative risks based on the account of losses associated with risk situations has been adduced. It has been proposed to carry out a quantitative risk assessment, which is demonstrated by the example of the assessment of various types of savings risk. Directions of reduction of risks of losses of credit consumer cooperatives have been designated. The necessity of identification of risks of credit consumer cooperatives for substantiation of strategy and tactics of cooperative development has been emphasized.